Statistical analysis in electromagnetic compatibility - Niewiadomski, Karol (2024)
Power electronic (PE) converters are electronic devices designed to process electrical power, transforming the input voltage into an output voltage with desired characteristics. Their main function, which is power conversion, is enabled through the usage of switching devices, such as transistors. Due to the rapid development of the Smart Grid (SG) power devices are more often used alongside or close to communication systems, in particular serial communication devices. The operation of the power converters might induce electromagnetic interference (EMI) and bring about malfunction of these communication devices, which poses a challenge in achieving electromagnetic compatibility (EMC) of the system. The range of switching frequencies used in modern power converters corresponds to the conducted EMI range (9 kHz – 30 MHz), and the impact of conducted EMI is highly influenced by the presence of parasitic elements, values of which exhibit uncertain behaviour due to environmental conditions, geometrical layouts of the circuits, and manufacturing tolerances of the circuit elements.